Endurance in extreme work environments. (November 2021) - Cham, Belinda S.; Boeing, Alexandra A.; Wilson, Michael David; Griffin, Mark A.; Jorritsma, Karina
Extreme work environments are inherently stressful and involve challenging working and living conditions. In contexts ranging from space exploration to disaster response, people must sustain performance under pressure, and function with limited resources. In this paper we develop the concept of endurance for extreme work environments, which we define as the capacity to sustain performance at high levels for safe and effective operations over extended durations (e.g., a mission, operation, deployment, or expedition). We integrate diverse streams of literature (e.g., work stress, recovery, and sleep) to describe endurance in terms of short- and long-term energy management processes as individuals interact with their work-life system (i.e. work, non-work, and sleep environment). We conclude with theoretical and practical implications for a better understanding of endurance, such as considering multiple time perspectives, and the role that researchers, practitioners, and organizations can play in optimizing endurance in the field.